1981
DOI: 10.1246/cl.1981.1529
|View full text |Cite
|
Sign up to set email alerts
|

THE STEREOSELECTIVE SYNTHESIS OF d-RIBULOSE

Abstract: In the presence of zinc halide, 2-furyllithium reacts with 2,3-O-isopropylidene-d-glyceraldehyde in a highly stereoselective manner to give the chiral and stereo-defined alcohol, 2,2-dimethyl-4-(2-furyl)hydroxymethyl-1,3-dioxolane, which is further elaborated to afford d-ribulose in three steps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…Of the two readily separated (flash chromatography) diastereoisomeric alcohols 12 (l-configuration) and 13 (u-configuration), one is formed preferentially, depending on the organometallic compound used: with MeLi, the attack occurs preferentially from the Re-face of the aldehyde-carbonyl plane (+ 12), with MeZnCI*) from the Si-face (chemical correlation as structure proof, see below). This result is reminiscent of Mukaiyama's observation in the addition of 2-furyl-metal derivatives to glyceraldehyde acetonide [8] At this point, we have shown that the dibromide 2 can be used for a number of conversions with introduction of new substituents in the 4-position of the butanoic-acid moiety. A crucial step is the subsequent hydrogenation of the dioxinone double bond with regeneration of a stereogenic center in the 6-position of the ring.…”
Section: See the Classical Investigations Bysupporting
confidence: 71%
“…Of the two readily separated (flash chromatography) diastereoisomeric alcohols 12 (l-configuration) and 13 (u-configuration), one is formed preferentially, depending on the organometallic compound used: with MeLi, the attack occurs preferentially from the Re-face of the aldehyde-carbonyl plane (+ 12), with MeZnCI*) from the Si-face (chemical correlation as structure proof, see below). This result is reminiscent of Mukaiyama's observation in the addition of 2-furyl-metal derivatives to glyceraldehyde acetonide [8] At this point, we have shown that the dibromide 2 can be used for a number of conversions with introduction of new substituents in the 4-position of the butanoic-acid moiety. A crucial step is the subsequent hydrogenation of the dioxinone double bond with regeneration of a stereogenic center in the 6-position of the ring.…”
Section: See the Classical Investigations Bysupporting
confidence: 71%
“…Registry No. 2,benzenethiol,2,4,tri-tert-butylthiobenzaldehyde, 84543-57-7. Communications Total Synthesis of (-)-Pseudopterosin A Summary: Pseudopterosin A has been synthesized, in optically active form, from (S)-(-)-limonene.…”
Section: Methodsmentioning
confidence: 99%
“…Addition of 60 (prepared quantitatively from dimethylzinc and TiC14 in CH2Clz) to the aldehyde 48 led to 63 and 64 in the ratio 92 : 65 66 a, R = nRu…”
Section: Other Organometallic Reagentsmentioning
confidence: 99%